Effects of synthetic cannabinoids on psychomotor, sensory and cognitive functions relevant for safe driving - Orazietti, Vasco; Basile, Giuseppe; Giorgetti, Raffaele; Giorgetti, Arianna (Frontiers in Psychiatry, 2022)
Recreational use of Synthetic Cannabinoids (SCs), one of the largest groups of Novel Psychoactive Substances (NPS), has increased globally over the past few years. Driving is a structured process requiring the cooperation of several cognitive and psychomotor functions, organized in different levels of complexity. Each of these functions can be affected when Driving Under the Influence (DUI) of SCs. In order to reduce the likelihood of SC-related road accidents, it is essential to understand which areas of psychomotor performance are most affected by these substances, as well as the severity of impairment. For this purpose, a multiple database- literature review of the most recent evidence regarding the psychomotor effects of SCs, as shown by experimental studies on humans and animals, has been performed. Despite the many limitations connected to experimental studies on humans, results showed a consistency between animal and human data. SCs appear to impair psychomotor performance in humans, affecting different domains related to safe driving even at low doses. Cases of DUI of SC have been repeatedly reported, although the exact prevalence is likely to be underestimated due to current analytical and interpretative issues. For this reason, an accurate physical examination performed by trained and experienced personnel has a primary role in recognizing signs of impairment in case of strong suspicion of SC consumption. The identification of a suspected case should be followed by reliable laboratory examination.